2017
DOI: 10.1111/ijfs.13375
|View full text |Cite
|
Sign up to set email alerts
|

Brewing with prolyl endopeptidase from Aspergillus niger : the impact of enzymatic treatment on gluten levels, quality attributes and sensory profile

Abstract: Beer is considered unsafe for those affected by coeliac disease because it is traditionally made by glutencontaining raw materials. During the stabilisation phase, the addition of processing aids leads to a gluten reduction, because the haze-forming activity of a protein in beer depends greatly on proline-rich barley hordeins. Prolyl endopeptidase (PE) is commonly used as a stabiliser in the brewing industry. This study was conducted to evaluate the impact of treatment with PE on gluten level, quality attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…PEPs including AN-PEP cleave proteins at proline (Pro, P) residues 25 and are able to degrade gluten owing to the high frequency of Pro (10−30%) found in gluten proteins. 26,27 The enzymatic detoxification of gluten has been recently reviewed by Wieser et al 28 In a series of studies employing the R5 competitive ELISA, 24,29,30 a range of commercial beers was analyzed, including those produced from nongluten-containing grains and from barley with and without PEP treatment. Of these, the beers employing PEP treatment were shown to yield a gluten content below the CODEX threshold of 20 mg/kg.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPs including AN-PEP cleave proteins at proline (Pro, P) residues 25 and are able to degrade gluten owing to the high frequency of Pro (10−30%) found in gluten proteins. 26,27 The enzymatic detoxification of gluten has been recently reviewed by Wieser et al 28 In a series of studies employing the R5 competitive ELISA, 24,29,30 a range of commercial beers was analyzed, including those produced from nongluten-containing grains and from barley with and without PEP treatment. Of these, the beers employing PEP treatment were shown to yield a gluten content below the CODEX threshold of 20 mg/kg.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a series of studies employing the R5 competitive ELISA, ,, a range of commercial beers was analyzed, including those produced from nongluten-containing grains and from barley with and without PEP treatment. Of these, the beers employing PEP treatment were shown to yield a gluten content below the CODEX threshold of 20 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…6 Thus, it is presumed that proteolysis of gluten with PEP during the brewing process leads to a reduction in the gluten concentration of beer. When analyzed by competitive enzymelinked immunosorbent assay (ELISA), beers brewed in the presence of PEP generally test for gluten concentrations of less than 20 ppm, 4,7,8 which is the internationally accepted threshold for gluten in foods that can be tolerated by most people with CD. 9,10 However, there is uncertainty in interpreting competitive ELISA results for the quantitation of hydrolyzed gluten in terms of equivalent amounts of intact gluten in hydrolyzed or fermented foods, such as beer.…”
mentioning
confidence: 99%
“…Thus, it is presumed that proteolysis of gluten with PEP during the brewing process leads to a reduction in the gluten concentration of beer. When analyzed by competitive enzyme-linked immunosorbent assay (ELISA), beers brewed in the presence of PEP generally test for gluten concentrations of less than 20 ppm, ,, which is the internationally accepted threshold for gluten in foods that can be tolerated by most people with CD. , However, there is uncertainty in interpreting competitive ELISA results for the quantitation of hydrolyzed gluten in terms of equivalent amounts of intact gluten in hydrolyzed or fermented foods, such as beer. ,− A study performed by Allred et al demonstrated that sera from a small subset of active-CD patients reacted to gluten that is present in beer brewed in the presence of PEP . This study suggests that some individuals in the celiac population could be sensitive to beers brewed in the presence of PEP.…”
mentioning
confidence: 99%
“…In fact, the exogenous enzymes added for gluten reduction negatively impact foam stability because of hordein hydrolysation. 16 In a previous study, we found a mean decrease of about 14% of foam stability after enzyme addition in three different kinds of beer, with an average value of about 230 s. 26 On the other hand, the use of gluten-free cereals and pseudocereals led to different results, with good foam stability for maize, unsatisfactory for amaranth, acceptable for quinoa and poor for oat. 16 We also found a value of 181 s for a beer of 100% malted teff 8 and a mean value of 164 s for bottom-fermented beer with 100% malted rice.…”
Section: Resultsmentioning
confidence: 90%